Fuzzy logic controller for DC motor position control - Nurainaa, Elias; Nafrizuan, Mat Yahya (Universiti Malaysia Pahang, 2018)
This paper presents the position control of DC motor by using a fuzzy logic controller (FLC) with MATLAB application. Firstly, the DC motor was modeled and converted to a subsystem in Simulink. Then the fuzzy logic controller is designed by using MATLAB toolbox. The scopes include the simulation and modeling of DC motor, fuzzy controller and different transfer function for DC motor model as a benchmark to the performance of the fuzzy system. The position control is an adaptation of assisted lifting device system. Fuzzy logic control can play an important role because knowledge-based design rules can be easily implemented in the system with unknown structure and it is going to be popular since the control design strategy is simple and practical. This makes FLC an alternative method used in a nonlinear industrial system. The results obtained from FLC are compared with different transfer function used for the dynamic response of the closed-loop system and also the system with and without a controller will be compared. Parameters such as peak position in degree, settling time in second and maximum overshoot in percent will be part of the simulation result. The overall performance shows that system with FLC performs better than compared to the system without FLC.